S18 Bronchoalveolar Lavage, Tracheal Wash and Induced Sputum Surfactant Phospholipid Kinetics from Healthy Volunteers. (19th November 2012) - Dushianthan, A; Cusack, R; Goss, V; Postle, AD; Grocott, MPW
Abstract : Introduction and Aims: Pulmonary surfactant is a complex mixture of lipoproteins synthesised and secreted by alveolar type II cells. The assessment of surfactant synthetic function and metabolism may provide essential information in disease states characterised by surfactant dysfunction. Airway surfactant is thought to be of alveolar origin. However, surfactant kinetics from airway secretions may vary from alveolar surfactant. Stable isotope labelling of surfactant precursors enables dynamic mapping of surfactant PC molecular species. This study aimed to compare three surfactant recovery methods [bronchoalveolar lavage (BAL), tracheal wash (TW) and induced sputum (IS)] to assess surfactant PC kinetics in healthy adults. Surfactant phosphatidylcholine (PC) is synthesised de novo from choline via CDP-choline pathway. By labelling choline with deuterium, a naturally occurring isotope of hydrogen, it is possible to assess surfactant PC synthesis and metabolism in humans. Methods: Healthy human volunteers had an infusion of methyl- D9-choline-chloride [3.6mg/kg] for 3 hours. BAL and TW specimens were taken at 24 and 48 hours and induced sputum samples were taken at 0, 8, 24, 48 and 96 hours after choline infusion. The lipid fraction was extracted with chloroform and methanol. The samples were analysed by triple quadrupole electro spray ionisation mass spectrometer (ESI/MS). The results are expressed in mean (+/–standard error of mean). Results: Ten healthy volunteers were recruited. The endogenous PC composition from BAL and TW were similar. The newly synthesised PC fraction mirrored the endogenous composition at 48 hours for both BAL and TW IS PC composition and D9 labelled PC fraction was variable. The total PC D9 -incorporation at 48 hours was higher than 24 hours for BAL (0.55±0.04%), TW (0.56±0.04%) and IS (0.58±0.06). PC16:0/16:0 D9 -incorporation had significant correlation for BAL and TW (r 2 =0.8201, P<0.05). Conclusions: Isotope labelling of choline using ESI/MS analytical method, it is possible to assess surfactant PC metabolism. The tracheal aspirate is an alternative technique to assess surfactant metabolism in patients otherwise unable to tolerate invasive bronchoscopy. This methodology may be utilised to assess surfactant synthetic function in patients with acute lung injury.